Sustaining angiosperms’ diversity of Bood Promontory and Eco-Park, Butuan City, Philippines: Step towards a community based-protection management program - Julie Berame; MINIE L. BULAY; RISSA M. MERCADO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Berame JS, Bulay ML, Mercado RM. 2021. Sustaining angiosperms’ diversity of Bood Promontory and Eco-Park, Butuan City, Philippines: Step towards a community based-protection management program. Biodiversitas 22: 2519-2527. Bood Promontory and Eco-Park (Butuan City, Philippines) is a non-protected 72-hectare agroforestry land, disputed by two barangays. Its existence is rich historically, but the presence of important plant species, the angiosperms, attracted people which caused their number declining recently. Therefore, this study explored the flora using a line transect method through random sampling to provide valuable inputs necessary to back up the promulgation for a community based-protection management program in the area. Results found that 291 angiosperms accounted for 11 tree species, 4 herbs, 1 shrub, and 5 unnamed species. Trees made up 75% of the area, dominated by Mahogany (Swietenia macrophylla, King), and 50% of plant species are unassessed. Yakal, Philippine Teak, Antipolo, Narra, Mahogany, and Molave are in the IUCN Redlist for critically endangered and vulnerable statuses commonly used for construction materials, boat making, furniture, carvings, plywood, and firewood, putting them into peril and destruction if left unprotected. There were no recognized organizations, yet partial participation of the barangay council in forest protection and monitoring management can help angiosperms sustaining their existence. The City Tourism and DENR have to accelerate the claim for protecting the area and implement fully functional participation of locals to sustain and protect the vulnerability of angiosperm species.